The quality of antenatal care services in Shivrajpur block of district Kanpur: a community based survey - Tiwari, Harish Chandra; Mishra, Richa (International Journal of Research in Medical Sciences, 2017)
Background: India is amongst the top five countries in terms of absolute numbers of maternal deaths. In Uttar Pradesh MMR is even higher than national average. In spite of better utilisation of ante-natal services, pregnancy outcome is not significantly improving. Reason behind it is that worrying gaps in quality of antenatal care exist which lead to poor effectiveness of ANC in practice. Methods: In the present study quality of antenatal care services utilised by 286 recently delivered women (RDWs) in last one year in Shivrajpur block of district Kanpur was conducted from August 2012 to July 2013. A predesigned questionnaire was used for data collection. Information regarding age, parity, and detailed history of antenatal care & place of antenatal care were collected after taking verbal consent. Results: Majority (76.1%) of women were within 20 to 30 year of age who had delivered in last one year while 13.6% of women were within 20 year of age. In present study we find 91.9% coverage of antenatal care which was based on receiving at least one antenatal check-up. Majority (73.1%) of women received antenatal care from public facility (SC/PHC/CHC/Govt. Hospital). Out of 263 RDWs who received ANC, three-fourths had weight measurement (74.9%), their abdomen examined (76.4%) and hemoglobin estimation (69.6%) done. Less than two-thirds had height (60.8%) and blood pressure measured (66.2%). Nearly one of the two RDWs had urine examination (50.2%) and told about pregnancy complications & danger signs. Only 14.8% RDWs consumed 100 IFA tablet. TT injection was received by 79.5% of RDWs. Full ANC was taken by only 16.3% RDWs. Conclusion: Poor qualities of antenatal have a limited potential to affect maternal mortality. High-risk screening during antenatal care, as a means of identifying women for facility-based intra-partum care, is not effective for women who subsequently failed to obtain complete package of antenatal care.